Pelatihan Penulisan Artikel Ilmiah Populer bagi Warga Pimpinan Cabang Istimewa Muhammadiyah Pakistan - Winny Perwithosuci; Imron Rosyadi (TAAWUN, 2024)
This community service activity aims to provide training in writing popular scientific articles to improve the quality of writing by At Tanwir magazine contributors. Activities are carried out online and using the lecture method. This activity was attended by 25 participants from PCIM and PCIA Pakistan. The result of this activity is an increase in participants' understanding regarding writing popular articles. Community service activities run smoothly and successfully. The training material for writing popular scientific articles contains four (4) topics, namely: (1) motivation for writing, (2) basis for writing, (3) tips and tricks for writing, and (4) several things that must be considered when writing opinions and columns. After the material delivery session was completed, it continued with a discussion and question and answer session. The discussion and question and answer sessions also went well. Many participants interacted with the resource person to discuss the material presented. In the future, it is recommended that there be more intensive follow-up activities to improve participants' writing skills.